LANDASAN ONTOLOGIS DALAM PENGEMBANGAN TEORI MANAJEMEN PENDIDIKAN ISLAM - Siti Baimunah; Kautsar Eka Wardhana; Yusnia Binti Kholifah (STKIP Subang, 2025)
This study explores ontological foundations in developing Islamic educational management theory through qualitative approach with case study method. Contemporary Islamic educational management complexity requires theoretical reconstruction integrating spiritual and material dimensions holistically to address traditional-modernity dichotomy challenges. Data collection conducted through semi-structured in-depth interviews with five key informants consisting of madrasah principals, pesantren directors, and Islamic higher education leaders, along with organizational documentation analysis using purposive sampling. Thematic analysis reveals five main ontological principles: tawhid in management, spiritual-material integration, khilafah in leadership, institutional amanah, and shura in decision-making. Findings demonstrate that Islamic Educational Management Framework successfully integrates operational efficiency with Islamic spiritual values, creating more participative organizational structures and istikharah-musyawarah based decision-making mechanisms with 83% stakeholder satisfaction rate. Transformational Islamic leadership typology shows highest effectiveness at 85%, while holistic evaluation systems using Islamic Performance Indicators measure dunyawi and ukhrawi dimensions simultaneously. Resulting theoretical construction not only provides alternatives for Islamic educational institutions but also contributes to enriching global educational management theory through spirituality dimension integration previously neglected in conventional literature.